Effect of Deposition Time on the Structural and Optical Properties of Molybdenum Chalcogenides Thin Films - T., Joseph Sahaya Anand; S, Shariza (NIMP Publishing House, 2011)
Molybdenum chalcogenides, specifically molybdenum selenide, MoSe2 and molybdenum sulphide, MoS2 thin films have been successfully deposited onto indium-tin-oxide (ITO) coated glass substrates and stainless steel substrates by electrodeposition technique. The effects of the deposition time on the growth, structural and optical properties of the films were then studied. X-ray diffraction (XRD) patterns have confirmed the polycrystalline rhombohedral MoSe2 and hexagonal MoS2 phase formation. The results show that the intensity of XRD peaks for these materials increases with the increase of deposition time. UV -VIS spectrophotometric measurement revealed that the optical band gap values of the thin films decreased with the increase of deposition time and lie in the range from 1.12 – 1.22 eV for MoSe2 and 1.65 – 1.74 eV for MoS2 thin films. Surface morphology studies by scanning electron microscopy showed uniform and continuous thin film with layered structure surface.